2020
DOI: 10.14203/jki.v14i2.476
|View full text |Cite
|
Sign up to set email alerts
|

Dimensi Mobilitas Penduduk: Berpindah, Bukan Untuk Menetap

Abstract: Significant improvement in information, communication and technology, followed by increased transportation access has made circular mobility much easier. Although circular mobility is not a well-established concept, it refers to repeated migration experiences between origin and destination areas, and there is no intention to stay permanently in any particular destination. This paper aims to assess current types of population mobility, with special focus on circular mobility. Besides literature review, the anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 7 publications
0
8
0
3
Order By: Relevance
“…In the IMWs context, their movement is under national or special parties' arrangement, and the processes are managed by agents that collaborate with the government or private labour-sending agencies. IMWs employed in the formal sector, such as factory workers and institutional caregivers, are taken to dormitories provided by their employers [ 67 ]. Moreover, those recruited in the domestic sector, such as housemaids and caregivers, are taken to their places of employment.…”
Section: Indonesian Migrant Workers' Vulnerability To Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…In the IMWs context, their movement is under national or special parties' arrangement, and the processes are managed by agents that collaborate with the government or private labour-sending agencies. IMWs employed in the formal sector, such as factory workers and institutional caregivers, are taken to dormitories provided by their employers [ 67 ]. Moreover, those recruited in the domestic sector, such as housemaids and caregivers, are taken to their places of employment.…”
Section: Indonesian Migrant Workers' Vulnerability To Covid-19mentioning
confidence: 99%
“…Domestic staff and caregivers stay at their employers' houses [ 74 ], while those that work in manufacturing industries live in dormitories, either within or outside the factory. Furthermore, plantation workers reside in barracks provided by the company in the vicinity [ 67 ]. IMWs that are fish workers in Taiwan spend quality time in the vessels with others.…”
Section: Indonesian Migrant Workers' Vulnerability To Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…The change in human movement in the form of a global cessation of movement is unprecedented. The implication for human mobility is a change in human mobility patterns during the Covid-19 pandemic [1].…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic is caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) virus which attacks the respiratory tract and is a dangerous infectious disease where transmission comes from human-to-human transmission through droplets, either directly or indirectly [4]. Romdiati revealed that population travel as the cause of the spread of the virus was evidenced at the beginning of this virus spreading to residents who traveled internationally, then spreading to local transmission [5]. This shows that travel and Kasihan Subdistrict during the COVID-19 pandemic by the Bantul Regency Health Office was classified as a moderate risk zone with a value of 2.0 or level 3 with the criteria that the area had a high risk of spreading COVID-19, and the spread and potential of the virus were out of control [6].…”
Section: Introductionmentioning
confidence: 99%